Archives and the Atlantic Pact: how the NATO Archives preserves and protects the records of an Alliance*. Issue 2 (1st August 2021) - Deserno, Ineke; Roche, Nicholas; Viallet, Barbara; Wintenberger, Etienne
Abstract : In 2019, the North Atlantic Treaty Organization (NATO) celebrated 70 years of consultation, consensus and conflict prevention. The same year also marked 20 years since NATO first opened access to its archives to the public. The establishment of the NATO Archives in 1999 was hailed by then Secretary General Javier Solana as an important signal of the Alliance's commitment to transparency and openness. NATO declassified and publicly disclosed thousands of documents and opened a dedicated Reading Room at NATO Headquarters in Brussels. Behind the scenes, the establishment of the NATO Archives and of the Archives Committee also changed the way in which NATO managed its historical records. Up to this point, there was no NATO-wide policy on archives, no organizational archives and no consistency in any of the traditional archival functions. Starting in 1999, NATO could boast a professional archives programme, implemented by trained archivists and governed by a committee of national experts. The programme can claim a string of successes over the last 20 years, implementing archival strategy in novel and unique ways to respond to NATO's organizational structure. While the Archives are part of NATO's political headquarters, NATO itself is composed of multiple formal entities under the overall direction of the North Atlantic Council and the Military Committee, including military commands, civilian agencies, military operations etc. Before 1999, each managed their archival material locally, according to internal procedures. This article outlines the Archives' strategic policies and its governance, involving national experts of all its 30 member nations; presents its increasingly larger and more robust acquisition programme based on a strong and actively managed retention and disposition strategy; assesses its digital preservation activities; and provides an update on NATO's declassification and public disclosure programme.